The coexistence of commodity money and Fiat money - Olivier Ledoit; Sébastian Lotz (University of Zurich, Department of Economics, 2011)
In reaction to the monetary turmoil created by the financial crisis of September 2008, both legislative and constitutional reforms have been proposed in different Countries to introduce Commodity Money alongside existing National Fiat Currency. A thorough evaluation of the Economic consequences of these new proposals is warranted. This paper surveys some of the existing knowledge in Monetary and Financial Economics for the purpose of answering the significant Economic questions raised by these new political initiatives.
Keywords: E42; E52; 330; Papierwährung; Vergleich; Währungssystem; Wirkungsanalyse; Schweiz